Transnational patterns among Asian American and Latina/o American children of immigrants from Southern California. - Trieu, Monica M.; Vargas, Nicholas; Gonzales, Roberto G. (Journal of Ethnic & Migration Studies, 2016)
A growing literature has examined the prevalence of transnational engagement among children of immigrants. However, few studies have been equipped to analyse underlying dynamics that serve to impede or perpetuate transnational practices among them in the United States. In this article, we compare transnationalism narratives between 1.5- and second-generation children of immigrants to more fully adjudicate enduring transnational ties over time. Our analysis of 134 interviews from the Children of Immigrants Longitudinal Study suggests that children of immigrants from Southern California conceptualise transnational experiences in diverse but remarkably similar ways. The meanings attached to transnational behaviours and identities employ certain patterns, and are often related to strength of kin-based ties, ethnic language fluency, and levels of structural access to the homeland. Moreover, findings indicate that the second-generation is nearly as transnationally engaged as the 1.5-generation. This provides novel but limited evidence in support of claims that transnational ties are sustained across generations.